Glial activation and inflammation along the Alzheimer’s disease continuum - Kaja Nordengen; Bjørn-Eivind Kirsebom; Kristi Henjum; Per Selnes; Berglind Gísladóttir; Marianne Wettergreen; Silje Bøen Torsetnes; Gøril Rolfseng Grøntvedt; Knut K. Waterloo; Dag Aarsland; Lars N. G. Nilsson; Tormod Fladby (Journal of Neuroinflammation, 2019)
Abstract Background Neuronal and glial cell interaction is essential for synaptic homeostasis and may be affected in Alzheimer’s disease (AD). We measured cerebrospinal fluid (CSF) neuronal and glia markers along the AD continuum, to reveal putative protective or harmful stage-dependent patterns of activation. Methods We included healthy controls (n = 36) and Aβ-positive (Aβ+) cases (as defined by pathological CSF amyloid beta 1-42 (Aβ42)) with either subjective cognitive decline (SCD, n = 19), mild cognitive impairment (MCI, n = 39), or AD dementia (n = 27). The following CSF markers were measured: a microglial activation marker—soluble triggering receptor expressed on myeloid cells 2 (sTREM2), a marker of microglial inflammatory reaction—monocyte chemoattractant protein-1 (MCP-1), two astroglial activation markers—chitinase-3-like protein 1 (YKL-40) and clusterin, a neuron-microglia communication marker—fractalkine, and the CSF AD biomarkers (Aβ42, phosphorylated tau (P-tau), total tau (T-tau)). Using ANOVA with planned comparisons, or Kruskal-Wallis tests with Dunn’s pairwise comparisons, CSF levels were compared between clinical groups and between stages of biomarker severity using CSF biomarkers for classification based on amyloid pathology (A), tau pathology (T), and neurodegeneration (N) giving rise to the A/T/N score. Results Compared to healthy controls, sTREM2 was increased in SCD (p < .01), MCI (p < .05), and AD dementia cases (p < .001) and increased in AD dementia compared to MCI cases (p < .05). MCP-1 was increased in MCI (p < .05) and AD dementia compared to both healthy controls (p < .001) and SCD cases (p < .01). YKL-40 was increased in dementia compared to healthy controls (p < .01) and MCI (p < .05). All of the CSF activation markers were increased in subjects with pathological CSF T-tau (A+T−N+ and A+T+N+), compared to subjects without neurodegeneration (A−T−N− and A+T−N−). Discussion Microglial activation as indicated by increased sTREM2 is present already at the preclinical SCD stage; increased MCP-1 and astroglial activation markers (YKL-40 and clusterin) were noted only at the MCI and AD dementia stages, respectively, and in Aβ+ cases (A+) with pathological T-tau (N+). Possible different effects of early and later glial activation need to be explored.